Fabrication and Dosimetric Characterization of Novel Bio-Based Tissue Substitute Phantom Materials - Damilola Oluwafemi Samson, Ahmad Shukri , Mohd Zubir Mat Jafri , Rokiah Hashim , Mohd Zahri Abdul Aziz , Mohd Fahmi Mohd Yusof (International Journal of Advanced Science and Technology, 2020)
construction is the deficiency of standardization background in practice codes for thesematerials, despite the fact it possess superior properties, such as Ultra-high Performance FiberReinforced Concrete (UHPFRC). In this study, Finite Element Analysis (FEA) is utilized tosimulate the behavior of UHPFRC and Normal Concrete (NC) simply supported beams understatic flexural loading. Abaqus software has been used in which a simplified version of theConcrete Damage Plasticity Model (CDPM) was chosen as a non-linear constitutive model. Themodel has been validated against conventional CDPM at global (load-deflection) and local(load-stain) levels. Reinforced UHPFRC beam models showed clearly matching response withthe validity research paper (reference study) experimental findings. The response of UHPFRCbeams has been compared to NC beams. This comparison has been explained in detail andchecked with similar material comparisons in the literature. The proposed study has revealedand compared the distribution of cracks in the form of tension and compression damage for bothmaterials. As a conclusion, modelling is an effective way to predict the behavior of concretebeams in which the relative local response was captured in reinforcement bars.